Características de la intervención profesional de las trabajadoras sociales que laboran en el área de recursos humanos de las empresas industriales de la región la libertad, durante el año 2014 - Ordoñez Costa, Fiorella Lisseth (2014)
This study is a descriptive research has been conducted on the sample of 26 social workers who work in the area of Human Resources 24 medium and large La Libertad region industrial enterprises and considered by the Ministry of Production. It has gotten to know the characteristics of professional intervention in this area of high interest for the (as) professionals recently graduated (as), and for those still pursuing undergraduate studies, identifying the research, promotion, administration and support social developed by the professional post to generate and / or strengthen the welfare of employees and their families. This research is based on quantitative data and qualitative data, reflected in professional testimonials, situations and experiences that meet detailed interviews allowed social workers subject to study industrial enterprises; for this methods were used: - deductive, analytic - ethnographic, inductive synthetic cases and statistical analysis; techniques: survey, structured interviews, observation, formal talks and photographic record; and instruments: fieldbook, survey questionnaire, interview guide, observation log, log interview, camera and recorder. The results obtained confirm that the social workers of industrial companies conduct research, promotion, administration and social assistance oriented partner and his family, thus covering the levels of intervention and case group large proportion, and directing action to various eterios groups: adults, youth, children, seniors. So the Social Work Company stands as one of the larger fields where professionals can size your action if they believe and want.